Targeting Colorectal Cancer Cells with Niosomes Systems Loaded with Two Anticancer Drugs Models; Comparative In Vitro and Anticancer Studies - Shaymaa Wagdy El-Far; Hadel A. Abo El-Enin; Ebtsam M. Abdou; Ola Elsayed Nafea; Rehab Abdelmonem (MDPI AG, 2022)
Colorectal cancer (CRC) is considered one of the most commonly diagnosed malignant diseases. Recently, there has been an increased focus on using nanotechnology to resolve most of the limitations in conventional chemotherapy. Niosomes have great advantages that overcome the drawbacks associated with other lipid drug delivery systems. They are simple, cheap, and highly stable nanocarriers. This study investigated the effectiveness of using niosomes with their amphiphilic characteristics in the incorporation of both hydrophilic and hydrophobic anticancer drugs for CRC treatment. Methods: Drug-free niosomes were formulated using a response surface D-optimal factorial design to study the cholesterol molar ratio, surfactant molar ratio and surfactant type effect on the particle size and Z-potential of the prepared niosomes. After numerical and statistical optimization, an optimized formulation having a particle size of 194.4 ± 15.5 nm and a Z-potential of 31.8 ± 1.9 mV was selected to be loaded with Oxaliplatin and Paclitaxel separately in different concentrations. The formulations with the highest entrapment efficiency (EE%) were evaluated for their drug release using the dialysis bag method, in vitro antitumor activity on HT-29 colon cancer cell line and apoptosis activity. Results: Niosomes prepared using d-α-tocopheryl polyethylene glycol 1000 succinate (TPGS) at a molar ratio 4, cholesterol (2 molar ratio) and loaded with 1 molar ratio of either Oxaliplatin or Paclitaxel provided nanosized vesicles (278.5 ± 19.7 and 251.6 ± 18.1 nm) with a Z-potential value (32.7 ± 1.01 and 31.69 ± 0.98 mV) with the highest EE% (90.57 ± 2.05 and 93.51 ± 2.97) for Oxaliplatin and Paclitaxel, respectively. These formulations demonstrated up to 48 h drug release and increased the in vitro cytotoxicity and apoptosis efficiency of both drugs up to twice as much as free drugs. Conclusion: These findings suggest that different formulation composition parameters can be adjusted to obtain nanosized niosomal vesicles with an accepted Z-potential. These niosomes could be loaded with either hydrophilic drugs such as Oxaliplatin or hydrophobic drugs such as Paclitaxel. Drug-loaded niosomes, as a unique nanomicellar system, could enhance the cellular uptake of both drugs, resulting in enhanced cytotoxic and apoptosis effects against HT-29 colon cancer cells. Oxaliplatin-niosomes and Paclitaxel-niosomes can be considered promising alternative drug delivery systems with enhanced bioavailability of these two anticancer drugs for colorectal cancer treatment.